Review on Manufacturing for Advancement of Industrial Revolution 4.0 - Adam, Anbia; Yusof, Yusri; Iliyas, Maznah; Saif, Yazid; Hatem, Noor (International Journal of Integrated Engineering, 2018)
The world today stands at the threshold of a new revolution, the fourth in the history of mankind. It is imperative to study the effects of Industrial Revolution 4.0 (also known as IR 4.0) to understand the benefit that it will provides for the affected groups majority. This paper consists of review for mostly on manufacturing sector in United Kingdom, Singapore, European Union, United States and China which reveals the rapid growth and the effect of Industrial Revolution 4.0 towards these countries and consequently the world. Manufacturing has increased economy in Singapore, where incomes for employed residents in manufacturing exceed others by 0.4 percent. Meanwhile in United Kingdom and European Union, manufacturing has accounted for 8% and 24% respectively for their national jobs. However, United States shows slow increase in manufacturing employment sector and still below 18 million (before recession in 2009). Nonetheless, the employment could be affected by vast use of automated machine,Â unlike China which has ratio of 40 machines to 10,000 workers.Â